Variasi Regim Lengas dan Suhu Tanah Pada Lahan yang Mengalami Penutupan Awan Rendah Berbasis Peta Terra Modis di Pulau Lombok - Reni Anggraeni; Mahrup Mahrup; IGM Kusnarta; Putu Silawibawa (Journal of Soil Quality and Management, 2022)
Soil moisture and temperature are parameters of soil physical properties that are closely related to climatic variations. Descriptive Research on "Variation of Moisture Regime and Soil Temperature on Land with Low Cloud Cover" has been done, to determine the variation of soil moisture and soil temperature on land with permanently low cloud cover based on the Terra Modis map on the island of Lombok. Low cloud cover data was obtained from Terra Modis satellite data which were delineated by Lombok maps. Daily rainfall data were collected from the Climatology Meteorology and Geophysics Agency (BMKG) Kediri Station. Moisture and soil temperature were measured periodically at 10 day intervals, for two consecutive months (March and April, 2020). The results showed that soil moisture varied temporally. Soil moisture content was higher in areas with low cloud cover in the dryland with soils type of Typic Eutrudept, Inceptisols order, than in areas without cloud permanent cover. Soil temperature in the open zone (without low cloud cover) was higher than in the zone that always experiences closure